2016
DOI: 10.1016/j.ejphar.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme versus angiotensin converting enzyme-2 selectivity of MLN-4760 and DX600 in human and murine bone marrow-derived cells

Abstract: Angiotensin-converting enzymes, ACE and ACE2, are key members of renin angiotensin system. Activation of ACE2/Ang-(1-7) pathway enhances cardiovascular protective functions of bone marrow-derived stem/progenitor cells. The current study evaluated the selectivity of ACE2 inhibitors, MLN-4760 and DX-600, and ACE and ACE2 activities in human (hu) and murine (mu) bone marrow cells. Assays were carried out in hu and mu mononuclear cells (MNCs) and huCD34+ cells or mu-lineage-depleted (muLin-) cells, human-recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…Moreover, all three inhibitors exerted a significantly higher inhibitory activity against soluble than membrane-bound forms of (m)ACE2 (near maximal mACE2 inhibition at 10 −6 M), being the isomer B more selective and effective than the racemate or the isomer A for mACE2 vs. mACE expressed on the surface of mononuclear cells (or CD34 hematopoietic progenitors) [114]. A second ACE2 inhibitor, Dx600, produced similar results to those obtained with the isomer B [114]. Another study evaluated the inhibitory activity of both MLN-4760 and DX600 (either the linear conformational form or the disulfide bridged cyclic variant) inhibitors.…”
Section: Safety and Efficacy Concerns Of Mln4760 And Dx600 Ace2 Inhibmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, all three inhibitors exerted a significantly higher inhibitory activity against soluble than membrane-bound forms of (m)ACE2 (near maximal mACE2 inhibition at 10 −6 M), being the isomer B more selective and effective than the racemate or the isomer A for mACE2 vs. mACE expressed on the surface of mononuclear cells (or CD34 hematopoietic progenitors) [114]. A second ACE2 inhibitor, Dx600, produced similar results to those obtained with the isomer B [114]. Another study evaluated the inhibitory activity of both MLN-4760 and DX600 (either the linear conformational form or the disulfide bridged cyclic variant) inhibitors.…”
Section: Safety and Efficacy Concerns Of Mln4760 And Dx600 Ace2 Inhibmentioning
confidence: 97%
“…Actually, several reports describing Dx600 inhibitor administration in mice suggest its safe use. Of interest, a report described its (safe) use alone (1 mg/kg per day) by nasal inhalation for 3 days in a mouse model of endotoxin-induced lung inflammation [121]; however, this inhibitor is less efficacious than MLN-4760 in inhibiting the soluble forms of human rACE2 [114,115]. Altogether these reports on administration of ACE2 inhibitors do not reveal significant adverse impacts or mortality in experimental animals, which suggests their safety in chronic administration.…”
Section: Safety and Efficacy Concerns Of Mln4760 And Dx600 Ace2 Inhibmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 20 years, MLN-4760 (imidazole) [ 79 , 80 , 81 ], captopril derivative [ 82 , 83 ], DX600 and TAPI-2 peptide [ 84 , 85 ], losartan and its derivatives (benzimidazole [ 56 , 82 , 86 , 87 ], chloroquine and its derivatives (quinolone) [ 88 ], diminazene aceturate [ 89 ], cepharanthine (alkaloid) [ 75 ], thiorphan (palmitoyl) [ 87 ], and N -(2-aminoethyl)-1 aziridineethanamine (amino ethyl) [ 90 ] were discovered to have potential as ACE2 inhibitors. However, caution should be taken because, although ACE1 inhibitors (such as captopril, enalapril, and lisinopril) and angiotensin II receptor blockers (ARB) (such as olmesartan, losartan, candesartan, and valsartan) do have inhibitory effects on ACE2 [ 91 ], several studies showed that these drugs can increase the ACE2 blood level [ 86 ], which will likely increase the risk of contracting SARS [ 92 ].…”
Section: Inhibitors Of Ace2mentioning
confidence: 99%
“…Evidence has shown that ACE2 locally expresses in human bone marrow-derived stem/progenitor cells (BMSPCs) and manipulates cytokine-sensing to promote skeletal repair [4] . ACE2 promotes AngII degradation and synthetizes Ang1-7, which perform functions by way of Mas receptor.…”
Section: Justification Of the Proposed Hypothesismentioning
confidence: 99%